Combined Effect of Co-trimoxazole Prophylaxis and Safe Water on Diarrhea Amongst HIV-Exposed Infants and People Living With HIV/AIDS: A Systematic Review - Chavura, Elton; Singini, Wales; Chidya, Russel; Mbakaya, Balwani Chingatichifwe (European Scientific Journal, ESJ, 2023)
Irrespective of co-trimoxazole prophylaxis, diarrhea among HIV-exposed infants (HEI) and people living with HIV (PLWHA) remains unacceptably high. We aimed to determine the combined effect of improved water supply interventions and co-trimoxazole prophylaxis on frequency and severity of diarrhea among HEI and PLWHA. Using key search terms of safe sanitation, improved water supply, WaSH, co-trimoxazole prophylaxis, HIV-exposed, PLWHA, morbidity, mortality, diarrhea; we searched for published articles in PubMed, EMBASE, PsycINFO, AMED, CINAHL, DOAJ and Google Scholar databases guided by the acceptance practice developed by PROSPERO and COCHRANE. A PRISMA flow diagram was used to explain on the number of articles retrieved, retained, excluded and justifications for every action. A Mixed Method Appraisal Tool (MMAT) was used to assess the quality of the methodology of the selected studies. Safe water supply interventions and co-trimoxazole prophylaxis together reduced diarrhea episodes by up to 67% (IRR _ 0.33, 95% CI 0.24–0.46, P < 0.0001). The combined interventions resulted in 27% risk reduction in HIV disease progression whilst safe water alone was associated with reductions in the longitudinal prevalence of reported diarrhea of up to 53% among HIV exposed infants aged ≤2 years (LPR = 0.47, 95% CI: 0.30–0.73, P < 0.001). An expanded WaSH response in fighting HIV is critical to prevent diarrhea and rapid disease progression. The protocol was published in the PROSPERO database with registration number CRD42021240512.